Inovasi dan Pembauran Genre dalam Pertunjukan Keroncong Wayang Gendut - Wrahatnala, Bondet (Resital: Jurnal Seni Pertunjukan, 2021)
This paper aims to discuss the forms of design and genre-mixing carried out by the Keroncong Wayang Gendut -Congwayndut-group in Surakarta, which tries to offer a state of wayang performance with a more interactive packaging. The universal evolution approach uses the analytical tool in this paper to examine the new elements offered by Congwayndut as a form of innovation in the puppet show. The research method used is qualitative with a descriptive model. The conceptual approach and research methods found that the creation and genre-mixing carried out by Congwayndut were implemented in music, stories, and performance forms. The use of keroncong's music with combos and contemporary bands is the main illustration in the show. They are still based on  Ramayana and Mahabharata's epics but actualized in current phenomena in society. Congwayndut's innovative form of performance is packaged in interactive language and builds closeness to the audience. It intended so that the messages and values to be conveyed will be readily accepted and understood by the audience, whose segmentation is the younger generation.